The Interdependency of Reporting Discretion and Informational Efficiency in Laboratory Markets. - Bloomfield, Robert (The Accounting Review, 1996)
Abstract Examines how the level of market efficiency influences managers' use of reporting discretion and how allowing reporting discretion alters market efficiency. Nature of price efficiencies; Managerial reporting discretion; Market responses; Pricing errors; Manager's exercise of reporting discretion.